Revitalizing education in rural and small schools: The role of AI in teachers' professional development - Giuseppina Rita Jose Mangione; Michelle Pieri; Francesca De Santis (Italian Journal of Educational Technology, 2024)
The article explores the intersection of artificial intelligence (AI) and the professional development of teachers, with a focus on small and rural schools. Following a scoping review conducted by the research group, the focus is placed on the analysis of three studies, each pertaining to three subtopics within the theme “AI and teacher professional development” that emerged from the mapping: the use of intelligent environments for teacher training, teachers’ perceptions of AI solutions to support their practice, and the development of intelligent agents to assist teaching. The research emphasizes the importance of teacher training in addressing the challenges posed by AI to bridge the gap between urban and rural schools. This opens to future scenarios that will be explored through interviews with national and international experts and a Delphi Study, aimed at identifying opportunities for small schools and developing guidelines to achieve convergence on potential interventions in non-standard educational contexts.